Patterns and Mechanisms of Ant Diversity in Two Types of Land Use within Protected Forest Area Sirimau City of Ambon Maluku Province - Latumahina, Fransina (Advances in Social Sciences Research Journal, 2018)
Ants are the biodiversity constituent of 30% of the total insect biomass, very sensitive to changes in habitat structure and the environment in which they live can be an indicator of habitat destruction and ecosystem stability. The research was carried out in Sirimau Protected Forest area of Ambon City on two types of land use - each of secondary dryland and dryland farming from August to December 2012. The objective of the study was to know the structure of the ant community in two types of land use and to measure the pattern of ant distribution and diversity. Measurement of ant diversity using the Transect Line Plot method through a sampling system of a population sample with a sample plot approach that is on a line drawn across each type of land use using three Pitfall Trap (PT) methods or trap trap, Bait Trap BT) used Sugar and Tuna as feed and Hand Collecting (HC) method (Hasimoto, 2001) and collected with 70% alcohol preservation. Determination of ant species diversity and ant typeness in each type of land use using Shanon-Wienner index with the help of Ecological Methodology 2nd Edition (Krebs, 2000), and Margalef index (Ludwig and Reynold, 1988). The results of the study found that the number of individuals on the secondary dry land was 47,672 dominated by Meranoplus bicolor and Crematogaster ampularis and on dry land agriculture of 65,413 dominated by Polirachis belicossa and Echinopla lineata-lineata. The diversity index in August in the secondary drylands was 3.33 and 3.31 in September while on dryland farms were 3.67 in August and 3.59 in September were high.